Electrochemical In Situ Hydrogen Peroxide Production Can Reduce Microbial Load in Bioponic Nutrient Solutions Derived from Organic Waste - Lukas Simon Kriem; Carsten Pietzka; Marc Beckett; Luisa Gärtling; Benjamin Wriedt (Agriculture, 2023)
Technological advancement in recent decades has allowed for crop cultivation in soilless controlled environments, known as hydroponics, and this is being employed in an increasing number of factories worldwide. With continued local and regional disruptions in the supply chain to provide mineral fertilizers, new pathways to generate nutrient solutions are being developed. One potential approach is the recovery of nutrients from organic waste and wastewater using bioponics. Bioponics refers to the biological mineralization of organic residues through processes such as anaerobic and aerobic digestion and the use of such organically produced nutrient solutions in hydroponic systems. However, without disinfection of the nutrient solution, the high microbial loads increase the risk of pathogens affecting plant and consumer health. In this work, electrochemical hydrogen peroxide (H2O2) demonstrated success in reducing microbial loads. Different scenarios of application were considered: (1) variation in the H2O2 concentration in the nutrient solution by dosing H2O2 from ex situ electrochemical production, (2) variation in the dosing time-dependent reaction between the nutrient solution and H2O2 produced ex situ, and (3) the in situ production of H2O2 of the organic nutrient solution. The highest tested H2O2 concentration of 200 mg L−1 showed a microbial load reduction of bacteria at 93.3% and of fungi at 81.2%. However, the in situ production showed the highest reduction rate for bacteria and fungi in bioponic nutrient solutions, where longer reaction times also impact microbial concentrations in situ. Final microbial reductions of 97.8% for bacteria and of 99.1% for fungi were determined after a H2O2 production time of 60 min. Overall, our results show that electrochemical H2O2 production can be used to disinfect bioponic nutrient solutions, and the production cell can be implemented in bioponic systems in situ.